2023
DOI: 10.1021/acscatal.2c04479
|View full text |Cite
|
Sign up to set email alerts
|

Design of SA-FLP Dual Active Sites for Nonoxidative Coupling of Methane

Abstract: Direct conversion of methane to value-added chemical products under nonoxidative conditions is one of the most effective routes but still faces eminent challenges due to thermodynamic constraints and the lack of efficient catalysts. Herein, we propose to construct “Single-Atom”-“Frustrated Lewis Pair” (SA-FLP) dual-active-site catalysts for nonoxidative coupling of methane (NOCM). The single-atom site is created by doping a Pt atom at the Ce site of the CeO2 surface. The FLP site is fabricated by removing oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…50 Meanwhile, the Chang group explored “Single Atom”-“Frustrated Lewis Pair” (SA-FLP) dual active site catalysts through theoretical calculations, applying them in NOCM. 51…”
Section: Photocatalysts For Pnocmmentioning
confidence: 99%
See 1 more Smart Citation
“…50 Meanwhile, the Chang group explored “Single Atom”-“Frustrated Lewis Pair” (SA-FLP) dual active site catalysts through theoretical calculations, applying them in NOCM. 51…”
Section: Photocatalysts For Pnocmmentioning
confidence: 99%
“…50 Meanwhile, the Chang group explored ''Single Atom''-''Frustrated Lewis Pair'' (SA-FLP) dual active site catalysts through theoretical calculations, applying them in NOCM. 51 In a recent development, the Zhang research group employed a strategy involving thermal reduction-induced phase transition to fabricate densely packed Frustrated Lewis Pairs (FLPs) on layered Nb 2 O 5 surfaces, rich in Nb-OH (LB sites) and low-valence Nb (LA sites). 52 Initially, electrons localized near the exposed Nb sites are transferred to the Nb-OH groups under photoexcitation, thereby increasing the strength of LA and LB sites and forming a more favorable polarizing environment.…”
Section: Flps Photocatalystsmentioning
confidence: 99%
“…Nonoxidative coupling of methane to more valuable hydrocarbons is a potential route for natural gas and biogas valorization. The pioneering study of a highly active and stable Fe©SiO 2 catalyst by Bao and co-workers led to a substantial research effort in this area. ,, The isolated Fe centers in the Fe©SiO 2 catalyst are argued to limit C–C coupling and, therefore, coke formation on the catalytic surface. Based on this insight, other catalysts containing isolated metal sites such as Pt/CeO 2 , Pt/C 3 N 4 , and Ru/TiO 2 have been explored for nonoxidative coupling of methane. Xie et al were the first to report on the use of Pt/CeO 2 with isolated Pt sites for the NOCM reaction .…”
mentioning
confidence: 99%
“…Isolated Pt on CeO 2 was predicted to exhibit the highest C 2 -hydrocarbon selectivity. Chang and co-workers reported that the active sites in Pt/CeO 2 involve two functionalities, namely, single Pt atoms close to a frustrated Lewis acid obtained upon oxygen removal from ceria, which are together involved in methane activation under NOCM conditions . Despite the growing interest in Pt/CeO 2 for the NOCM reaction, it remains unclear how isolated Pt sites behave under harsh reaction conditions.…”
mentioning
confidence: 99%
“…Unfortunately, only a small amount of methane is used as chemical feedstock relative to the total amount produced because of the high stability of methane, where C–H bond energy values are 439 kJ mol –1 . , Thus, activation and conversion of methane to chemical high-value products have become a great challenge for catalysis researchers. In fact, methane can be activated with two different processes, i.e., the direct and indirect routes. The indirect route is to first convert methane to syngas (CO and H 2 ) followed by further conversion to other chemical products. , This route is energetically and economically expensive, due to the applied high operating pressures and temperatures. The direct route can realize the methane conversion via several pathways, for example, the partial methane oxidation, the oxidative coupling of methane (OCM), and the nonoxidative coupling of methane (NOCM). Among these direct conversion pathways, the nonoxidative catalytic methane conversion has received great attention. Bao et al reported a single iron embedded in the silica matrix is active for direct nonoxidative conversion of methane to C 2 product (ethylene) and aromatics without coke formation.…”
mentioning
confidence: 99%